Narrowing the Agronomic Yield Gaps of Maize by Improved Soil, Cultivar, and Agricultural Management Practices in Different Climate Zones of Northeast China - Liu, Z. J.; Yang, X. G.; Lin, Xiaomao; Hubbard, K. G.; Lv, S.; Wang, J. (My University, 2016)
Northeast China (NEC) is one of the major agricultural production areas in China, producing about 30% of China's total maize output. In the past five decades, maize yields in NEC increased rapidly. However, farmer yields still have potential to be increased. Therefore, it is important to quantify the impacts of agronomic factors, including soil physical properties, cultivar selections, and management practices on yield gaps of maize under the changing climate in NEC in order to provide reliable recommendations to narrow down the yield gaps. In this study, the Agricultural Production Systems Simulator (APSIM)-Maize model was used to separate the contributions of soil physical properties, cultivar selections, and management practices to maize yield gaps. The results indicate that approximately 5%, 12%, and 18% of potential yield loss of maize is attributable to soil physical properties, cultivar selection, and management practices. Simulation analyses showed that potential ascensions of yield of maize by improving soil physical properties PAY(s), changing to cultivar with longer maturity PAY(c), and improving management practices PAY(m) for the entire region were 0.6, 1.5, and 2.2 ton ha(-1) or 9%, 23%, and 34% increases, respectively, in NEC. In addition, PAY(c) and PAY(m) varied considerably from location to location (0.4 to 2.2 and 0.9 to 4.5 ton ha(-1) respectively), which may be associated with the spatial variation of growing season temperature and precipitation among climate zones in NEC. Therefore, changing to cultivars with longer growing season requirement and improving management practices are the top strategies for improving yield of maize in NEC, especially for the north and west areas.
Citation: Liu, Z. J., Yang, X. G., Lin, X. M., Hubbard, K. G., Lv, S., & Wang, J. (2016). Narrowing the Agronomic Yield Gaps of Maize by Improved Soil, Cultivar, and Agricultural Management Practices in Different Climate Zones of Northeast China. Earth Interactions, 20, 18. doi:10.1175/ei-d-15-0032.1
Keywords: Geographic Location/Entity; Asia; Variability; Climate Variability; Applications; Crop Growth